1995
DOI: 10.1007/bf00294693
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial biogenesis in temperature-sensitive cell division cycle mutants of Saccharomyces cerevisiae

Abstract: The temperature-sensitive cell division cycle (cdc) G1 mutants cdc28 and cdc35 show decreased mitochondrial volumes with respect to the wild type strain A364A (WT) at the restrictive temperature. Of the three criteria of mitochondrial biogenesis studied, that is, number of mitochondria per cell, relative area of the cell occupied by mitochondria, or relative area of mitochondria occupied by inner membranes, only the second indicator was significantly lower in cdc mutants than in the WT. The mitochondrial inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The results shown in Figures 4 and 5 and unpublished data support the latter idea, and further suggest that there is a threshold in the length of G1 below which the kinase expresses to higher levels. Furthermore, several cdc mutants showed a strong carbon and energetic uncoupling as well as decreased mitochondrial biogenesis during arrest of cell proliferation at the restrictive temperature Genta et al, 1995;Mónaco et al, 1995). It was suggested that the latter effects could be linked to carbon catabolite repression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results shown in Figures 4 and 5 and unpublished data support the latter idea, and further suggest that there is a threshold in the length of G1 below which the kinase expresses to higher levels. Furthermore, several cdc mutants showed a strong carbon and energetic uncoupling as well as decreased mitochondrial biogenesis during arrest of cell proliferation at the restrictive temperature Genta et al, 1995;Mónaco et al, 1995). It was suggested that the latter effects could be linked to carbon catabolite repression .…”
Section: Discussionmentioning
confidence: 99%
“…A likely interpretation of the latter results was that growth on gluconeogenic carbon sources, that occurs at slower rates than on glucose, might require a dose of the p34 CDC28 kinase low enough to be accomplished by the cdc28 mutant under these conditions . It has been suggested that the strong carbon and energetic uncoupling exhibited by several cdc mutants during arrest of cell proliferation at the restrictive temperature, could be linked to carbon catabolite repression Genta et al, 1995;Monaco et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the original CDC alleles, which cause cell cycle defects when grown at the non-permissive temperature, were later discovered to also result in reduced carbon metabolism and lower ATP production [61] . Conversely, mutations in cell cycle genes, such as the cyclin-dependent kinase CDC28 were found to also affect mitochondria biogenesis [62] . This metabolism-cell cycle connection has been studied in detail in budding yeast.…”
Section: The Mitochondria Meets the Cell Cyclementioning
confidence: 99%
“…[20] This argument is further supported by studies involving yeast cell division cycle (cdc) mutants. Interestingly, cdc28 and cdc35 show decreased mitochondrial biogenesis[21] and cdc5 and cdc27 show defects in mitochondrial segregation[22] as well as in nuclear division. Other examples include cdc8 and cdc21 mutants defective in nuclear DNA replication during the S phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%